The Influence Of Social Media Marketing And Store Environment On Purchase Decision Of Ms Glow Skincare Product - Siara, Sabina; Astuti Sudirman, Hudyah; Hadi Saputra, Praja (Fakultas Ekonomi Universitas Gresik, 2023)
The development of the skincare product business requires business people to understand consumer behavior in order to meet their needs. Social media marketing and store environment are adapted as factors that can influence consumer behavior before making a purchase decision. The influence of digital transformation trends and how they affect their collaboration will be investigated in depth in this study with a quantitative approach, using a survey questionnaire from 150 consumers, sampling using random sampling, used multiple regression tests as data analysis, hypothesis testing using the coefficient of determination test (R2), and partial test (t test). Data processing uses the SPSS version 29 program and shows the results that social media marketing and store environment can significantly influence purchasing decisions for MS Glow Samarinda skincare products